Hubungan Antara Penggarap Sawah Dengan Tuan Tanah Dalam Pemberian Upeti Di Desa Leguderu Kecamatan Boawae Kabupaten Nagekeo - Yosef Dentis; Marianus Nuwa Gu (Program Studi Pendidikan Ekonomi, Universitas Flores, 2021)
The problems raised in this study are: (1) What is the special relationship between landlords and rice cultivators in giving tribute in Leguderu Village, Boawae District, Nagekeo Regency? (2) What is the form of tribute given by cultivators to landlords in Leguderu Village?. The objectives of the study were: (1) To find out the special relationship between landlords and rice cultivators in giving tribute in Leguderu Village, Boawae District, Nagekeo Regency. (2) To find out the form of tribute given by cultivators to mosalaki in Leguderu Village, Boawae District, Nagekeo Regency. In this study the author uses the theory of symbolic interactionism. The approach used is a qualitative approach. Data collection techniques used in this study were: (1) Observation, (2) Interview, (3) Documentation. Data analysis techniques used in this study were: Data reduction, data presentation and verification or conclusion drawing. Based on the results of this study, the research can conclude that the special relationship between cultivators and landlords in giving tribute is a form of symbolic interaction. By giving tribute, friendship and kinship relations will be maintained between the cultivators and landlords. And advice to the younger generation to always understand and appreciate the land that has been given by the landlord